A catalyst for promoting hydrolysis of secondary aluminum dross and a preparation method and application thereof
Patent Information
- Application Number
- CN202511607444.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-05
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-11-05
AI Technical Summary
此外,铅、镉、铬等重金属离子的溶出,会造成土壤重金属超标,导致耕地退化,且重金属难以降解,对生态环境构成长期威胁
[0026]本申请提供一种促进二次铝灰水解的催化剂及其制备方法和应用。首先,改性介孔二氧化硅载体表面接枝的氨基(-NH2)和磺酸基(-SO3H)双官能团通过氢键和配位作用与活性组分紧密结合,将活性组分稳定固载;活性组分中改性偏铝酸钠由三乙醇胺与偏铝酸钠中的Al3+配位得到,三乙醇胺的胺基与羟基通过孤对电子与Al3+形成稳定螯合物,一方面避免改性偏铝酸钠中Al3+在碱性条件下过早生成Al(OH)3沉淀,另一方面通过三乙醇胺的碱性官能团提供弱碱性微环境,该微环境为催化剂体系对AlN和单质铝的水解提供了持续稳定的OH-供给源。
Smart Images

Figure CN121338839B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of secondary aluminum ash recycling technology, specifically to a catalyst for promoting the hydrolysis of secondary aluminum ash, its preparation method, and its application. Background Technology
[0002] Secondary aluminum ash is a major hazardous solid waste in the electrolytic aluminum and recycled aluminum industries, with an annual output exceeding 5 million tons, and its production is increasing year by year with the rapid development of the aluminum industry. In electrolytic aluminum production, a large amount of primary aluminum ash is generated during the processes of changing electrolytic cells, tapping aluminum, and dust removal in the purification system. The residue remaining after the extraction of metallic aluminum is secondary aluminum ash. In the recycled aluminum smelting process, the covering agent added during the remelting of aluminum ingots reacts with the molten aluminum, also generating a large amount of secondary aluminum ash.
[0003] The environmental risks posed by this solid waste are highly insidious and persistent. Elemental aluminum (Al) and aluminum nitride (AlN) undergo violent hydrolysis in water. Elemental aluminum reacts slowly with water, releasing hydrogen gas (flammable and explosive), and the resulting Al(OH)3 colloid encapsulates itself, hindering further reaction. AlN, on the other hand, hydrolyzes, continuously releasing ammonia gas, causing not only pungent odor pollution but also disrupting soil pH balance and inhibiting plant growth at high concentrations. Fluorides are highly corrosive; seeping into water bodies can kill aquatic life, and long-term accumulation through the food chain can harm human bones and the nervous system. Furthermore, the leaching of heavy metal ions such as lead, cadmium, and chromium can cause soil heavy metal contamination, leading to farmland degradation. These heavy metals are difficult to degrade, posing a long-term threat to the ecological environment.
[0004] Existing hydrolysis processes suffer from significant technical bottlenecks, primarily due to the low conversion rates of elemental aluminum and AlN. Traditional methods rely on single alkaline catalysts such as Na₂CO₃ and NaOH, with conversion rates rarely exceeding 95%. These reactions require prolonged exposure to high temperatures, resulting in high energy consumption and, due to excessively strong local alkalinity in the reaction system, hindering the conversion of AlN. 3+ The rapid formation of Al(OH)3 colloids creates a dense coating layer on the surface of aluminum ash particles, hindering the contact between water molecules and the internal AlN, resulting in a generally low hydrolysis rate. For example, Chinese Patent CN111874931A discloses a secondary aluminum ash harmless treatment process using sodium carbonate catalysis. Although the initial hydrolysis rate can reach 85%, after 2 hours of reaction, the Mg in the aluminum ash... 2+ Fe 3+ Metal ions form hydroxide precipitates through surface adsorption, which together with the Al(OH)3 coating layer constitute a double barrier, reducing the hydrolysis rate in the later stage and severely restricting the efficiency of harmless disposal of secondary aluminum ash.
[0005] In summary, to solve the above problems, there is an urgent need for a highly efficient catalyst to provide a solution for the application of secondary aluminum ash in the field of environmental remediation materials. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this application provides a catalyst for promoting secondary aluminum ash hydrolysis, its preparation method, and its application. The catalyst is prepared by supporting modified sodium aluminate, copper salt, hydroxylated alkylbenzene sulfonate, and polycarboxylate active components on modified mesoporous silica. By catalyzing the secondary aluminum ash hydrolysis, the hydrolysis rates of elemental aluminum and aluminum nitride are improved.
[0007] To achieve the above objectives, this application adopts the following technical solution:
[0008] In a first aspect, this application provides a catalyst for promoting the hydrolysis of secondary aluminum ash, comprising: a modified mesoporous silica support and an active component supported on the support; the modified mesoporous silica support is obtained by grafting amino and sulfonic acid bifunctional groups onto the surface of the mesoporous silica support; the active component comprises modified sodium aluminate, copper salt, hydroxylated alkylbenzene sulfonate sodium and polycarboxylate; the modified sodium aluminate is prepared by coordination between triethanolamine and sodium aluminate; the hydroxylated alkylbenzene sulfonate sodium is prepared by hydroxylation reaction between alkylbenzene sulfonate sodium and hydroxylating agent.
[0009] In this application, firstly, the amino (-NH2) and sulfonic acid (-SO3H) bifunctional groups grafted onto the surface of the modified mesoporous silica support tightly bind to the active component through hydrogen bonding and coordination, thus stably immobilizing the active component; the modified sodium aluminate in the active component reacts with the Al in the sodium aluminate through triethanolamine. 3+ Coordination yields triethanolamine's amino and hydroxyl groups via lone pair electrons with Al. 3+ The formation of stable chelates avoids the presence of Al in modified sodium aluminate. 3+ Premature formation of Al(OH)3 precipitate under alkaline conditions, coupled with the weakly alkaline microenvironment provided by the basic functional groups of triethanolamine, creates a stable OH- precipitate environment for the hydrolysis of AlN and elemental aluminum by the catalyst system. - Supply source.
[0010] Secondly, in a weakly alkaline microenvironment, the Al provided by modified sodium aluminate... 3+ Cu provided by copper salt 2+ Due to the spatial confinement effect of the carrier's mesoporous channels, they are closely arranged near the active sites, forming Al 3+ -Cu 2+ Activation center. Cu 2+ Due to its strong Lewis acidity, it preferentially coordinates with the N in AlN or the surface of elemental aluminum in secondary aluminum ash, thereby weakening the bond energy of Al-N and Al-Al bonds through electron cloud shift polarization. 3+ Cu through coordination regulation 2+ The electron cloud density, and the carrier sulfonic acid groups further stabilize Cu through electrostatic interactions.2+ The active state retains its Lewis acidity while inhibiting Cu. 2+ With OH - Excessive binding leads to inactivation, thereby lowering the energy barrier of the hydrolysis reaction.
[0011] Finally, the hydrophobic ends of hydroxylated alkylbenzene sulfonate anchor the hydrophobic surface of the secondary aluminum ash, while its hydrophilic sulfonate groups and the polar groups of triethanolamine face the aqueous phase, reducing the solid-liquid interfacial tension and thus accelerating the penetration of water into the internal pores of the secondary aluminum ash particles. Furthermore, the polycarboxylate avoids its own aggregation through electrostatic repulsion with the carrier sulfonate groups, and its carboxyl groups bind to the aluminum ash particles through electrostatic adsorption, interacting with Al... 3+ Cu 2+ The formation of weak coordination prevents particle agglomeration caused by metal ions, ensuring that AlN and elemental aluminum in secondary aluminum ash are always exposed to the active component's range of action, thereby increasing the hydrolysis rate of aluminum nitride and elemental aluminum in secondary aluminum ash.
[0012] Preferably, the amino group is introduced by an aminosilane coupling agent, and the sulfonic acid group is introduced by 3-(trihydroxysilyl)-propanesulfonic acid; the aminosilane coupling agent is at least one selected from 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.
[0013] Preferably, the copper salt is at least one of copper nitrate, copper chloride, and copper acetate.
[0014] Preferably, the sodium alkylbenzene sulfonate is at least one of sodium dodecylbenzene sulfonate, sodium tetradecylbenzene sulfonate, and sodium hexadecylbenzene sulfonate; and the hydroxylating agent is at least one of ethylene oxide, propylene oxide, and epichlorohydrin.
[0015] Preferably, the polycarboxylate is at least one selected from sodium polyacrylate, sodium polymethacrylate, and sodium polyaspartate.
[0016] Secondly, this application provides a method for preparing a catalyst that promotes the hydrolysis of secondary aluminum ash, comprising the following steps:
[0017] S1. Tetraethyl orthosilicate and anhydrous ethanol were mixed, ammonia was added, and the mixture was stirred at room temperature. CTAB (hexadecyltrimethylammonium bromide) was added as a template agent, and stirring continued. After filtration and washing, the template agent was removed by calcination to obtain a mesoporous silica support. The mesoporous silica support was dispersed in anhydrous ethanol and heated. An aminosilane coupling agent was added first, and the reaction was stirred. Then 3-(trihydroxysilyl)-propanesulfonic acid was added, and the reaction was stirred. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a modified mesoporous silica support.
[0018] S2. Dissolve sodium aluminate in deionized water and stir in a water bath until completely dissolved; add triethanolamine dropwise, continue stirring, and cool to room temperature to obtain modified sodium aluminate; dissolve sodium alkylbenzene sulfonate in deionized water; add hydroxylation reagent, heat, and stir to react; after the reaction is complete, cool to room temperature to obtain hydroxylated alkylbenzene sulfonate.
[0019] S3. The modified mesoporous silica carrier is dispersed in the modified sodium aluminate and ultrasonically impregnated; copper salt and polycarboxylate are added under a nitrogen atmosphere and stirred for the first time; then hydroxylated alkylbenzene sulfonate sodium is added, the pH is adjusted, and stirred for the second time to obtain the loaded material.
[0020] S4. The loaded material is dried under reduced pressure to obtain the catalyst.
[0021] Preferably, in step S1, the mass ratio of tetraethyl orthosilicate to anhydrous ethanol is 1:(10-13); the concentration of ammonia is 23wt.%-28wt.%; the mass ratio of ammonia to tetraethyl orthosilicate is 1:(40-60); the mass ratio of CTAB to tetraethyl orthosilicate is 1:(45-60); the calcination temperature is 550-600℃, and the time is 5-6h; the mass ratio of mesoporous silica support to anhydrous ethanol is 1:(15-30); the mass ratio of mesoporous silica support, aminosilane coupling agent, and 3-(trihydroxysilyl)-propanesulfonic acid is 1:(0.1-2):(0.1-2); the heating temperature is 40-60℃; the stirring reaction time is 2-4h; and the continued stirring reaction time is 3-5h.
[0022] Preferably, in step S2, the mass ratio of sodium aluminate to triethanolamine is 1:(0.5-1); the water bath temperature is 50-60℃, and the time is 2-3h; the mass ratio of sodium alkylbenzene sulfonate to deionized water is 1:(50-200); the mass ratio of sodium alkylbenzene sulfonate to hydroxylation reagent is 1:(0.1-0.3); the heating temperature is 50-70℃, and the stirring reaction is carried out for 2-3h.
[0023] Preferably, in step S3, the mass ratio of the modified mesoporous silica carrier, modified sodium aluminate, copper salt, polycarboxylate, and hydroxylated alkylbenzene sulfonate is 1:(0.05-0.1):(1.2-2.0):(0.3-0.5):(0.2-0.3); the ultrasonic impregnation power is 300-500W and the time is 1.5-2.5h; the first stirring temperature is 30-40℃ and the time is 1-1.5h, the second stirring temperature is 40-50℃ and the time is 30-60min; the pH range is 10-12; the vacuum drying temperature is 80-85℃, the vacuum degree is -0.08 to -0.1MPa, and the drying time is 4-6h.
[0024] Thirdly, this application provides a catalyst for promoting the hydrolysis of secondary aluminum ash in the process of secondary aluminum ash hydrolysis.
[0025] Compared with the prior art, the beneficial effects of this application are as follows:
[0026] This application provides a catalyst for promoting the hydrolysis of secondary alumina ash, its preparation method, and its application. First, amino (-NH2) and sulfonic acid (-SO3H) bifunctional groups grafted onto the surface of a modified mesoporous silica support are tightly bound to the active component through hydrogen bonding and coordination, thus stably immobilizing the active component. The modified sodium aluminate in the active component is formed by the reaction of triethanolamine with Al in sodium aluminate. 3+ Coordination yields triethanolamine's amino and hydroxyl groups via lone pair electrons with Al. 3+ The formation of stable chelates helps to prevent the formation of Al in modified sodium aluminate. 3+ Under alkaline conditions, Al(OH)3 precipitate forms prematurely. On the other hand, the basic functional groups of triethanolamine provide a weakly alkaline microenvironment, which provides a continuous and stable OH- precipitate for the hydrolysis of AlN and elemental aluminum by the catalyst system. - Supply source.
[0027] Secondly, in a weakly alkaline microenvironment, the Al provided by modified sodium aluminate... 3+ Cu provided by copper salt 2+ Due to the spatial confinement effect of the carrier's mesoporous channels, they are closely arranged near the active sites, forming Al 3+ -Cu 2+ Activation center. Cu 2+ Due to its strong Lewis acidity, it preferentially coordinates with the N in AlN or the surface of elemental aluminum in secondary aluminum ash, thereby weakening the bond energy of Al-N and Al-Al bonds through electron cloud shift polarization; simultaneously, Al 3+ Cu through coordination regulation 2+ The electron cloud density, and the carrier sulfonic acid groups further stabilize Cu through electrostatic interactions. 2+ The active state retains its Lewis acidity while inhibiting Cu. 2+ With OH - Excessive binding leads to inactivation, thereby lowering the energy barrier of the hydrolysis reaction.
[0028] Finally, the hydrophobic ends of hydroxylated alkylbenzene sulfonate anchor the hydrophobic surface of the secondary aluminum ash, while its hydrophilic sulfonate groups and the polar groups of triethanolamine face the aqueous phase, reducing the solid-liquid interfacial tension and thus accelerating the penetration of water into the internal pores of the secondary aluminum ash particles. Furthermore, the polycarboxylate avoids its own aggregation through electrostatic repulsion with the carrier sulfonate groups, and its carboxyl groups bind to the aluminum ash particles through electrostatic adsorption, interacting with Al... 3+ Cu 2+The formation of weak coordination prevents particle agglomeration caused by metal ions, ensuring that AlN and elemental aluminum in secondary aluminum ash are always exposed to the active component's range of action, thereby increasing the hydrolysis rate of aluminum nitride and elemental aluminum in secondary aluminum ash. Attached Figure Description
[0029] Figure 1 This is a schematic diagram of the process for preparing a catalyst that promotes secondary aluminum ash hydrolysis according to this application.
[0030] Figure 2 This is a graph showing the hydrolysis time-hydrolysis rate of aluminum nitride in Example 1 and Comparative Examples 1-3 of this application. Detailed Implementation
[0031] To make the technical problems, technical solutions, and beneficial effects to be solved by this application clearer, the application will be further described in detail below with reference to embodiments. However, this should not be construed as limiting the scope of this application to the following examples. All other embodiments obtained by those skilled in the art without creative effort without departing from the above-described methodological spirit of this application are within the scope of protection of this application.
[0032] In this application, the terminology used is for the purpose of describing particular embodiments only and is not intended to be limiting of this application.
[0033] The singular forms “for,” “or,” “a,” “any,” and “the” used in this application are intended to include the plural forms unless the context clearly indicates otherwise.
[0034] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.
[0035] The following describes in detail, with reference to different embodiments, a method for preparing a catalyst that promotes the hydrolysis of secondary aluminum ash provided in this application.
[0036] Example 1
[0037] like Figure 1 As shown, this embodiment provides a method for preparing a catalyst to promote the hydrolysis of secondary aluminum ash, including the following steps:
[0038] S1. Tetraethyl orthosilicate and anhydrous ethanol are mixed at a mass ratio of 1:10. Ammonia solution with a concentration of 23 wt.% is added, with a mass ratio of ammonia solution to tetraethyl orthosilicate of 1:40. The mixture is stirred at room temperature. CTAB is added as a template agent, with a mass ratio of CTAB to tetraethyl orthosilicate of 1:45. The mixture is stirred further. After filtration and washing, the template agent is removed by calcination at 550°C for 5 hours to obtain a mesoporous silica support. The mesoporous silica support is dispersed in anhydrous ethanol, wherein the mesoporous... The mass ratio of silica support to anhydrous ethanol was 1:15; the temperature was raised to 40℃; 3-aminopropyltriethoxysilane was added first, and the mixture was stirred for 2 hours; then 3-(trihydroxysilyl)-propanesulfonic acid was added, and the mixture was stirred for another 3 hours; the mass ratio of mesoporous silica support, 3-aminopropyltriethoxysilane, and 3-(trihydroxysilyl)-propanesulfonic acid was 1:0.1:0.1. After the reaction was completed, the mixture was filtered, washed, and dried to obtain the modified mesoporous silica support.
[0039] S2. Dissolve sodium aluminate in deionized water and stir in a 50°C water bath for 2 hours until completely dissolved. Add triethanolamine dropwise at a rate of 5 mL / min to make the mass ratio of sodium aluminate to triethanolamine 1:0.5. Continue stirring and cool to room temperature to obtain modified sodium aluminate. Mix sodium dodecylbenzenesulfonate and deionized water at a mass ratio of 1:50. Add ethylene oxide, wherein the mass ratio of sodium dodecylbenzenesulfonate to ethylene oxide is 1:0.1. Heat to 50°C and stir for 2 hours. After the reaction is complete, cool to room temperature to obtain hydroxylated sodium dodecylbenzenesulfonate.
[0040] S3. The modified mesoporous silica carrier is dispersed in modified sodium aluminate and ultrasonically impregnated for 1.5 hours at an ultrasonic power of 300W. Under a nitrogen atmosphere, copper nitrate and sodium polyacrylate are added, and the mixture is stirred for the first time and reacted at 30°C for 1 hour. Then, hydroxylated sodium dodecylbenzene sulfonate is added, wherein the mass ratio of modified mesoporous silica carrier, modified sodium aluminate, copper nitrate, sodium polyacrylate and hydroxylated sodium dodecylbenzene sulfonate is 1:0.05:1.2:0.3:0.2. The pH is adjusted to 10, and the mixture is stirred for the second time for 30 minutes to obtain the loaded material.
[0041] S4. The loaded material was dried under reduced pressure at 80℃ and a vacuum of -0.09MPa for 4 hours to obtain a catalyst that promotes the hydrolysis of secondary aluminum ash.
[0042] Example 2
[0043] like Figure 1 As shown, this embodiment provides a method for preparing a catalyst to promote the hydrolysis of secondary aluminum ash, comprising the following steps:
[0044] S1. Tetraethyl orthosilicate and anhydrous ethanol were mixed at a mass ratio of 1:12. 25 wt.% ammonia water was added, with a mass ratio of ammonia water to tetraethyl orthosilicate of 1:50. The mixture was stirred at room temperature. CTAB was added as a template agent, with a mass ratio of CTAB to tetraethyl orthosilicate of 1:50. The mixture was stirred further. After filtration and washing, the mixture was calcined at 580℃ for 5.5 hours to remove the template agent, yielding a mesoporous silica support. The mesoporous silica support was dispersed in anhydrous ethanol, with a mass ratio of mesoporous silica support to anhydrous ethanol of 1:20. The temperature was raised to 50℃. 3-Aminopropyltrimethoxysilane was added first, and the mixture was stirred for 3 hours. Then 3-(trihydroxysilyl)-propanesulfonic acid was added, and the mixture was stirred for 4 hours. The mass ratio of the mesoporous silica support, 3-aminopropyltrimethoxysilane, and 3-(trihydroxysilyl)-propanesulfonic acid was 1:1:1. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a modified mesoporous silica support.
[0045] S2. Dissolve sodium aluminate in deionized water and stir in a water bath at 55°C for 2.5 h until completely dissolved. Add triethanolamine dropwise at a rate of 6 mL / min to make the mass ratio of sodium aluminate to triethanolamine 1:0.8. Continue stirring and cool to room temperature to obtain modified sodium aluminate. Mix sodium tetradecylbenzenesulfonate and deionized water at a mass ratio of 1:100, add propylene oxide, wherein the mass ratio of sodium tetradecylbenzenesulfonate to propylene oxide is 1:0.2. Heat to 60°C and stir for 2.5 h. After the reaction is complete, cool to room temperature to obtain hydroxylated sodium tetradecylbenzenesulfonate.
[0046] S3. The modified mesoporous silica carrier is dispersed in modified sodium aluminate and ultrasonically impregnated for 2 hours at an ultrasonic power of 400W. Under a nitrogen atmosphere, copper chloride and sodium polymethacrylate are added, and the mixture is stirred for the first time and reacted at 35°C for 1.2 hours. Then, sodium hydroxylated tetradecylbenzenesulfonate is added, wherein the mass ratio of modified mesoporous silica carrier, modified sodium aluminate, copper chloride, sodium polymethacrylate and sodium hydroxylated tetradecylbenzenesulfonate is 1:0.08:1.8:0.4:0.25. The pH is adjusted to 11, and the mixture is stirred for the second time for 40 minutes to obtain the loaded material.
[0047] S4. The loaded material was dried under reduced pressure at 83℃ and a vacuum of -0.08MPa for 5 hours to obtain a catalyst that promotes the hydrolysis of secondary aluminum ash.
[0048] Example 3
[0049] like Figure 1 As shown, this embodiment provides a method for preparing a catalyst to promote the hydrolysis of secondary aluminum ash, comprising the following steps:
[0050] S1. Support Synthesis: Tetraethyl orthosilicate and anhydrous ethanol were mixed at a mass ratio of 1:13, and 28 wt.% ammonia water was added, with a mass ratio of ammonia water to tetraethyl orthosilicate of 1:60. The mixture was stirred at room temperature. CTAB was added as a template agent, with a mass ratio of CTAB to tetraethyl orthosilicate of 1:60. The mixture was stirred further. After filtration and washing, the template agent was removed by calcination at 600℃ for 6 hours to obtain a mesoporous silica support. The mesoporous silica support was dispersed in anhydrous ethanol, wherein the mesoporous silica support and anhydrous ethanol... The mass ratio of water to ethanol was 1:30; the temperature was raised to 60℃; N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was added first, and the mixture was stirred for 4 hours; then 3-(trihydroxysilyl)-propanesulfonic acid was added, and the mixture was stirred for another 5 hours; wherein the mass ratio of mesoporous silica support, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 3-(trihydroxysilyl)-propanesulfonic acid was 1:2:2. After the reaction was completed, the mixture was filtered, washed, and dried to obtain the modified mesoporous silica support.
[0051] S2. Modification of sodium aluminate: Sodium aluminate was dissolved in deionized water and stirred in a water bath at 60°C for 3 hours until completely dissolved; triethanolamine was added dropwise at a rate of 7 mL / min to make the mass ratio of sodium aluminate to triethanolamine 1:1, stirring was continued, and the mixture was cooled to room temperature to obtain modified sodium aluminate; sodium hexadecylbenzenesulfonate and deionized water were mixed at a mass ratio of 1:200, epichlorohydrin was added, wherein the mass ratio of sodium hexadecylbenzenesulfonate to epichlorohydrin was 1:0.3, the temperature was raised to 70°C, and the reaction was stirred for 3 hours; after the reaction was completed, the mixture was cooled to room temperature to obtain hydroxylated sodium hexadecylbenzenesulfonate.
[0052] S3. Active component loading: The modified mesoporous silica support was dispersed in modified sodium aluminate and ultrasonically impregnated for 2.5 hours at an ultrasonic power of 500W. Under a nitrogen atmosphere, copper acetate and sodium polyaspartate were added, and the mixture was stirred for the first time and reacted at 40°C for 1.5 hours. Then, sodium hexadecylbenzenesulfonate was added, wherein the mass ratio of modified mesoporous silica support, modified sodium aluminate, copper acetate, sodium polyaspartate and sodium hexadecylbenzenesulfonate was 1:0.1:2.0:0.5:0.3. The pH was adjusted to 12, and the mixture was stirred for the second time for 60 minutes to obtain the loaded material.
[0053] S4. Post-treatment: The loaded material is dried under reduced pressure at 85℃ and a vacuum of -0.1MPa for 6 hours to obtain a catalyst that promotes the hydrolysis of secondary aluminum ash.
[0054] Comparative Example 1
[0055] This comparative example provides a method for preparing a catalyst that promotes the hydrolysis of secondary aluminum ash. The difference between this method and Example 1 is that 3-aminopropyltriethoxysilane and 3-(trihydroxysilyl)-propanesulfonic acid are not used to modify the mesoporous silica support in S1. Other operating steps and process parameters are exactly the same as in Example 1.
[0056] Comparative Example 2
[0057] This comparative example provides a method for preparing a catalyst that promotes the hydrolysis of secondary aluminum ash. The difference between this method and Example 1 is that modified sodium aluminate is not prepared in S2, and unmodified sodium aluminate is added in S3. Other operating steps and process parameters are exactly the same as in Example 1.
[0058] Comparative Example 3
[0059] This comparative example provides a method for preparing a catalyst that promotes secondary aluminum ash hydrolysis. The difference between this method and Example 1 is that hydroxylated alkylbenzene sulfonate is not prepared in S2, and unhydroxylated alkylbenzene sulfonate is added in S3. Other operating steps and process parameters are exactly the same as in Example 1.
[0060] Performance Testing and Methods:
[0061] Secondary aluminum ash: Taken from an aluminum plant, its main components (wt.%) include AlN 28.5%, elemental Al 12.3%, Al2O3 35.2%, SiO2 8.7%, and fluorides 3.1%. It is pulverized to 150 mesh and dried at 105℃ for 2 hours for later use.
[0062] Hydrolysis reaction conditions: Divide the secondary aluminum ash into six parts, so that the mass ratio of secondary aluminum ash to catalyst is 30:1, the mass ratio of deionized water to total solids is 6:1, the reaction temperature is 50℃, the mechanical stirring speed is 200rpm, and the reaction time is 2 hours.
[0063] 1. Aluminum nitride hydrolysis rate test: The above-mentioned secondary aluminum ash was divided into six parts and hydrolyzed with Examples 1-3 and Comparative Examples 1-3 respectively. The volume of NH3 produced by the reaction was determined by the water displacement method. The formula is: hydrolysis rate = (actual NH3 production / theoretical NH3 production) × 100%.
[0064] 2. Hydrolysis rate test of elemental aluminum: The elemental aluminum samples screened from the secondary aluminum ash were divided into six parts and hydrolyzed with Examples 1-3 and Comparative Examples 1-3 respectively. After the reaction, the remaining solids were separated and the content of unhydrolyzed elemental aluminum was determined by chemical analysis. The hydrolysis rate was calculated as (initial amount of elemental aluminum - remaining amount) / initial amount × 100%.
[0065] 3. Catalyst reaction rate test: The above-mentioned secondary aluminum ash was divided into six parts and hydrolyzed with Examples 1-3 and Comparative Examples 1-3 respectively. The time to reach 90% aluminum nitride hydrolysis rate was recorded.
[0066] 4. Catalyst stability test: After the catalyst is recycled 5 times, the aluminum nitride hydrolysis rate of the 5th reaction is measured (the catalyst is washed with water and dried at 60°C after each reaction).
[0067] Table 1 Performance test data of the catalysts prepared in Examples 1-3 and Comparative Examples 1-3
[0068]
[0069] From Table 1 and Figure 2 It can be seen that in the aluminum nitride hydrolysis rate test, the aluminum nitride hydrolysis rate in the example group reached 99.9%, which was significantly better than that in the comparative group (94.5%-95.7%). The modified mesoporous silica support in Examples 1-3, through its surface amino and sulfonic acid bifunctional groups, provides a highly efficient loading platform for the active components via hydrogen bonding and coordination, enabling Al... 3+ With Cu 2+ Al forms within the channel 3+ -Cu 2+ Bimetallic activation centers; in which Cu 2+ By leveraging Lewis acid activation of the Al-N bond to lower the reaction energy barrier, Al 3+ Adjusting Cu 2+ Electron cloud density prevents deactivation, while hydroxylated alkylbenzene sulfonate and polycarboxylate synergistically disperse secondary aluminum ash particles. Combined with the mass transfer advantages of the mesoporous support, this ensures sufficient contact between AlN and the active components, accelerating AlN hydrolysis. Comparative Example 1 uses an unmodified mesoporous silica support, lacking both amino and sulfonic acid bifunctional groups. This results in uneven loading of the active components and an inability to synergistically construct a stable, weakly alkaline microenvironment, increasing mass transfer resistance and leading to incomplete AlN hydrolysis. Comparative Example 2 does not contain triethanolamine, and the Al in sodium aluminate... 3+ It easily forms Al(OH)3 precipitate, leading to OH... - Supply fluctuations make AlN surfaces prone to precipitation and coverage, leading to a decrease in hydrolysis rate. Comparative Example 3 uses unhydroxylated sodium alkylbenzene sulfonate, which cannot form hydrogen bonds with the sulfonic acid groups of the support for stable adsorption. The solid-liquid interfacial tension is difficult to reduce, resulting in insufficient water penetration, limited Al-N bond activation efficiency, and hindered hydrolysis reaction.
[0070] In the hydrolysis rate test of elemental aluminum, the 99.9% of the example group was significantly higher than that of the comparative group (94.9%-95.8%). Example 1 used a modified mesoporous silica carrier synthesized with CTAB. Its ordered mesoporous structure physically isolates Al(OH)3 generated on the surface of elemental aluminum, preventing the formation of a dense passivation layer. Simultaneously, its high specific surface area allows for the interaction of aluminum powder with water molecules and OH groups.- Sufficient contact channels are provided; and the copper salt loaded on the support forms an "Al-Cu" micro-battery with aluminum. Aluminum acts as the anode, continuously oxidizing and dissolving, while copper acts as the cathode, accelerating electron transfer and completely destroying the Al2O3 oxide film on the aluminum surface. Combined with 300-500W ultrasonic impregnation, the active components are uniformly dispersed in the mesoporous channels, forming high-density catalytic sites, ensuring complete participation of aluminum powder in the reaction. Comparative Example 1 uses an unmodified support, and the system lacks an ordered mesoporous structure. Al(OH)3 easily accumulates on the aluminum surface, with approximately 4%-5% of elemental aluminum being encapsulated and unable to react, resulting in a decreased hydrolysis rate. Comparative Example 2 does not contain triethanolamine, allowing free Al... 3+ It readily forms Al(OH)3 precipitate, is unstable in alkaline environments, and OH... - The efficiency of destroying the oxide film on the aluminum surface is reduced, and the hydrolysis rate decreases. Comparative Example 3 uses unhydroxylated alkylbenzene sulfonate, which has poor interfacial dispersion, aluminum particles are easy to agglomerate, and lacks hydroxyl-assisted penetration. Some elemental aluminum is covered by the oxide film, and the hydrolysis rate is reduced by about 4.4%.
[0071] In the catalyst reaction rate test, the example group required 145-152 minutes to reach 90% AlN hydrolysis rate, which was 28%-53% higher than the comparative group. The modified mesoporous support in the examples, through its pore confinement effect, enriched AlN particles (<100nm), increasing the local reactant concentration; simultaneously, ultrasonic impregnation uniformly embedded active components such as copper salt and modified sodium aluminate into the mesopores. Combined with the synergistic effect of the bimetallic activation centers and interface-optimized components, this significantly reduced the activation energy and accelerated the reaction kinetics. The comparative groups experienced rate lag due to mass transfer or activation barriers: the unmodified support in Comparative Example 1 lacked mesoporous confinement, resulting in low reactant diffusion efficiency and a significantly prolonged time to reach 90% hydrolysis rate; Comparative Example 2, due to Al… 3+ Precipitation reduces the number of active sites, slows reaction initiation, and increases the time to reach the target hydrolysis rate. In Comparative Example 3, the unhydroxylated alkylbenzene sulfonate sodium cannot effectively optimize interfacial mass transfer and lacks the synergistic effect of hydroxyl groups and the support. The reaction activation energy is not sufficiently reduced, and the rate is limited by the natural breaking efficiency of Al-N bonds, resulting in the longest reaction time.
[0072] In the catalyst cycle stability test, the AlN hydrolysis rate of the example group remained at 98.3%-98.8% after 5 cycles, which was much higher than that of the comparative group (82.6%-88.5%). The active component in the examples achieved stable loading through multiple mechanisms: the silanol groups (-SiOH-) on the surface of the mesoporous silica formed Si-O-Al covalent bonds with the modified sodium aluminate, and coordinate bonds with the copper salt. Combined with the deep penetration effect of ultrasonic impregnation, the detachment rate of the active component was significantly reduced. Simultaneously, the polymer chains of the polycarboxylate were wrapped around the mesopores, further fixing the active component and inhibiting loss during recycling. The comparative group experienced activity decay due to poor loading stability: the unmodified support of Comparative Example 1 could only physically adsorb the active component without chemical bond anchoring, making it prone to detachment due to stirring and friction; after 5 cycles, the hydrolysis rate was only 86.1%. Comparative Example 2 did not add triethanolamine, and free Al... 3+ During the cycle, Al(OH)3 precipitate was continuously generated and washed away with water, and the active component was continuously reduced. After 5 cycles, the hydrolysis rate dropped to 82.6%. In Comparative Example 3, the unhydroxylated alkylbenzene sulfonate sodium was easily released from the system, and the interface optimization effect gradually weakened. In addition, AlN particles easily adsorbed impurities and covered the active sites. After 5 cycles, the hydrolysis rate dropped to 88.5%.
[0073] In summary, the catalysts in the example group that promote the hydrolysis of secondary aluminum ash achieved high aluminum nitride hydrolysis rate, high metallic aluminum hydrolysis rate, fast reaction rate and excellent cycle stability through support structure design, synergistic effect of active components and process optimization, demonstrating their technical advantages in the resource utilization of secondary aluminum ash.
[0074] The above results demonstrate and describe the basic principles and main features of this application, as well as its advantages.
[0075] Those skilled in the art should understand that this application is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of this application. Various changes and modifications can be made to this application without departing from the spirit and scope thereof, and all such changes and modifications fall within the scope of this application as claimed. The scope of protection of this application is defined by the equivalents of the appended claims.
Claims
1. A catalyst for promoting the hydrolysis of secondary aluminum ash, characterized in that, include: Modified mesoporous silica support and active components supported on the support; The modified mesoporous silica support is obtained by grafting amino and sulfonic acid bifunctional groups onto the surface of the mesoporous silica support; the active components include modified sodium aluminate, copper salt, hydroxylated alkylbenzene sulfonate sodium and polycarboxylate; the modified sodium aluminate is prepared by coordination of triethanolamine and sodium aluminate; the hydroxylated alkylbenzene sulfonate sodium is prepared by hydroxylation reaction of alkylbenzene sulfonate sodium and hydroxylating agent.
2. The catalyst for promoting secondary aluminum ash hydrolysis according to claim 1, characterized in that, The amino group is introduced by an aminosilane coupling agent, and the sulfonic acid group is introduced by 3-(trihydroxysilyl)-propanesulfonic acid; the aminosilane coupling agent is at least one selected from 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.
3. The catalyst for promoting secondary aluminum ash hydrolysis according to claim 2, characterized in that, The copper salt is at least one of copper nitrate, copper chloride, and copper acetate.
4. The catalyst for promoting secondary aluminum ash hydrolysis according to claim 3, characterized in that, The sodium alkylbenzene sulfonate is at least one of sodium dodecylbenzene sulfonate, sodium tetradecylbenzene sulfonate, and sodium hexadecylbenzene sulfonate; the hydroxylating agent is at least one of ethylene oxide, propylene oxide, and epichlorohydrin.
5. The catalyst for promoting secondary aluminum ash hydrolysis according to claim 4, characterized in that, The polycarboxylate is at least one of sodium polyacrylate, sodium polymethacrylate, and sodium polyaspartate.
6. A method for preparing a catalyst that promotes the hydrolysis of secondary aluminum ash, used to prepare the catalyst of claim 5, characterized in that, Includes the following steps: S1. Tetraethyl orthosilicate and anhydrous ethanol were mixed, ammonia was added, and the mixture was stirred at room temperature. CTAB was added as a template agent, and stirring was continued. After filtration and washing, the template agent was removed by calcination to obtain a mesoporous silica support. The mesoporous silica support was dispersed in anhydrous ethanol and heated. First, an aminosilane coupling agent was added, and the mixture was stirred to react. Then, 3-(trihydroxysilyl)-propanesulfonic acid was added, and the mixture was stirred to react. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a modified mesoporous silica support. S2. Dissolve sodium aluminate in deionized water and stir in a water bath until completely dissolved; add triethanolamine dropwise, continue stirring, and cool to room temperature to obtain modified sodium aluminate; dissolve sodium alkylbenzene sulfonate in deionized water; add hydroxylation reagent, heat, and stir to react; after the reaction is complete, cool to room temperature to obtain hydroxylated alkylbenzene sulfonate. S3. Disperse the modified mesoporous silica carrier in the modified sodium aluminate and impregnate it with ultrasonication. Under a nitrogen atmosphere, copper salt and polycarboxylate were added and stirred for the first time; then sodium hydroxylated alkylbenzene sulfonate was added, the pH was adjusted, and a second stirring was performed to obtain the loaded material. S4. The loaded material is dried under reduced pressure to obtain the catalyst.
7. A method for preparing a catalyst to promote secondary aluminum ash hydrolysis according to claim 6, wherein in step S1, the mass ratio of tetraethyl orthosilicate to anhydrous ethanol is 1:(10-13); the concentration of ammonia is 23wt.%-28wt.%; the mass ratio of ammonia to tetraethyl orthosilicate is 1:(40-60); the mass ratio of CTAB to tetraethyl orthosilicate is 1:(45-60); the calcination temperature is 550-600℃, and the time is 5-6h; the mass ratio of mesoporous silica support to anhydrous ethanol is 1:(15-30); the mass ratio of mesoporous silica support, aminosilane coupling agent, and 3-(trihydroxysilyl)-propanesulfonic acid is 1:(0.1-2):(0.1-2); the heating temperature is 40-60℃; the stirring reaction time is 2-4h; and the continued stirring reaction time is 3-5h.
8. The method for preparing a catalyst to promote secondary aluminum ash hydrolysis according to claim 6, wherein in step S2, the mass ratio of sodium aluminate to triethanolamine is 1:(0.5-1); the water bath temperature is 50-60℃, and the time is 2-3h; the mass ratio of sodium alkylbenzene sulfonate to deionized water is 1:(50-200); the mass ratio of sodium alkylbenzene sulfonate to hydroxylation reagent is 1:(0.1-0.3); the heating temperature is 50-70℃, and the stirring reaction is carried out for 2-3h.
9. A method for preparing a catalyst to promote secondary alumina hydrolysis according to claim 6, wherein in step S3, the mass ratio of the modified mesoporous silica support, modified sodium aluminate, copper salt, polycarboxylate, and hydroxylated alkylbenzene sulfonate is 1:(0.05-0.1):(1.2-2.0):(0.3-0.5):(0.2-0.3); the ultrasonic impregnation power is 300-500W, and the time is 1.5-2.5h; the first stirring temperature is 30-40℃, and the time is 1-1.5h; the second stirring temperature is 40-50℃, and the time is 30-60min; the pH range is 10-12; the vacuum drying temperature is 80-85℃, the vacuum degree is -0.08 to -0.1MPa, and the drying time is 4-6h.
10. The application of a catalyst for promoting secondary aluminum ash hydrolysis according to any one of claims 1-5 in the secondary aluminum ash hydrolysis process.
Citation Information
Patent Citations
Secondary aluminum ash harmless treatment process
CN111874931A
Recovery and reutilization method of hydrogenation catalyst waste material
CN108620083A
Supported copper-based catalyst preparation method and applications of supported copper-based catalyst in synthesis of ethylene glycol
CN110694672A